Renato Rizzi. Teatro Elisabettiano di Danzica - Mugnai, Francesca (Firenze Architettura, 2021)
The landscape and the history of Gdansk are represented in the synthesis expressed by the architecture of the theatre in which Renato Rizzi resorts to ‘mechanical’ art with the same spirit of a Renaissance architect or artist wishing to transfer into his own ‘creation’ the harmony of the Universe, and for whom the ‘machine’ is a mirror of Nature. The ‘machine’ is the place where archè and téchne meet.